SAT0621 Validation Study of Predictive Value of Capillaroscopic Skin Ulcer Risk Index (CSURI) in Scleroderma Patients Treated with Bosentan. (9th June 2015) - Sebastiani, M.; Cestelli, V.; Manfredi, A.; Praino, E.; Cannarile, F.; Spinella, A.; Colaci, M.; Giuggioli, D.; Ferri, C.
Abstract : Background: CSURI is a capillaroscopic index, able to identify scleroderma (SSc) patients at high risk for new or non-healing digital ulcers (DU) in the next three months. CSURI has been validated, only in patients not treated with bosentan, in a large multicenter study in 2011. Objectives: To evaluate the predictive value of CSURI in SSc patients assuming bosentan for the prevention of DU. Methods: Seventy-six consecutive SSc patients treated with bosentan were enrolled in a multicenter study (F/M 4.4/1; mean age 56.4±13.6 years; diffuse/limited cutaneous subset 30/44). All patients undergone to NVC and CSURI was calculated according to published studies. At baseline all patients had a history of at least one DU in the last year, and 26 patients (30.3%) showed a current DU. At the time of the study 76.3% of patients were also treated with intravenous prostanoids, while no patients was assuming bosentan for pulmonary arterial hypertension. Results: After 3 months from NVC 18/26 patients showed non healing ulcers and 18/76 patients developed new DU. Receiver operator characteristic curve, performed to analyze the prognostic accuracy of CSURI in regard to DU development, is reported in the figure . The area under the curve (AUC) was 0.69 (95% CI 0.57-0.79, p=0.0019) and the higher sensitivity and specificity were observed for a CSURI value of 2.5 (sensitivity 94.4; specificity 57.5; positive and negative likehood ratio 2.22 and 0.097, respectively). At the validated cut-off value of 2.96 sensitivity was 86.1%, specificity 60.0%, positive and negative likehood ratio 2.15 and 0.23, respectively, showing a lower negative predictive value. Conclusions: In patients treated with bosentan, CSURI shows a lower positive predictive value if compared with SSc population observed in our previous validation study, while the negative predictive value can be considered acceptable. The cause of this different result is not evaluable by our study. SSc peripheral microangiopathy is sustained by a multifactorial process, only partially known, involving a complex cytokines and cells network. In this picture, bosentan could reduce the incidence of new DU, without significantly interfere with the parameters included in CSURI calculation. Some Authors observed a general improvement of NVC parameters in SSc patients treated with bosentan. These data are not in contrast with our study since CSURI calculation is obtained by considering the "worst" capillaroscopic image. Moreover, a longer period of observation as in the other studies should more significantly influence changes in NVC parameters. In our previous studies, CSURI showed a higher predictive value than history of DU in detecting SSc patients at risk for new lesions. Anyway in this study this role of primary prevention cannot be applicable. Moreover, a special attention could be pointed on patients with recurrent DU, regardless specific treatments. A combined approach based on clinical picture and CSURI could probably help in managing therapy of SSc patients with DU, but only prospective clinical trial could clarify the correct role of NVC in the evaluation and management of vasoactive treatments. Disclosure of Interest: None declared